AUDIO VISUAL METHODS ON THE KNOWLEDGE AND ATTITUDES OF TEENAGERS REGARDING HIV-AIDS AT SMAN 2 Central CIKARANG IN 2023 - Imtisalillah, Mujtahidah; Rohmah, Hajar Nur Fathur (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
The incidence of deaths due to HIV-AIDS among young people throughout the world shows an alarming trend. Statistical data shows that every day, 4000 people, including 1100 young people (aged 15-24 years), are infected with HIV. The research aimed to assess the impact of HIV-AIDS health education media using audio-visual methods on adolescents' knowledge and attitudes at SMAN 2 Central Cikarang. The research, conducted in 2023, utilized a pre-experimental design with a pretest-posttest one-group setup. The study population comprised all SMAN 2 Central Cikarang students, totaling 814 individuals, with a sample size of 86 chosen through non-probability purposive sampling. The research instrument was a questionnaire. Statistical analysis using the Wilcoxon Signed Rank Test revealed a significant influence, as evidenced by an increase in the average knowledge and attitude scores of the teenagers regarding HIV-AIDS following the health education intervention (p-value = 0.000). This suggests a positive impact of audio visual methods on adolescents' understanding and perceptions of HIV-AIDS.